2023
DOI: 10.1021/acsami.3c07140
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Highly Luminescent Quasi Two-Dimensional CsPbBr3 Perovskite Films in High Humidity Air for Light-Emitting Diodes

Abstract: Perovskite light-emitting diodes (LEDs) have attracted extensive attention in recent years due to their outstanding performance and promise in lighting and display applications. However, the fabrication of perovskite LEDs usually requires a low-humidity atmosphere, which is unfavorable for industrial production. Herein, we report an effective strategy to fabricate highly luminescent quasi two-dimensional CsPbBr3 perovskite films in an ambient atmosphere with a humidity up to 60%. We reveal that the hole transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Figure 2a,b shows the Ni 2p spectra of the pristine NiO x and PSSNa-modified NiO x films. By fitting the XPS results, 16 it can be seen that Ni 2+ and Ni 3+ components exist in both films, and the signals at 853.9 eV are attributed to the NiO and the 855.6 and 857.5 eV signals correspond to the Ni 2p of Ni 2 O 3 and NiOOH, respectively. 32−34 It is found that the PSSNa modification increases the Ni 3+ /Ni 2+ ratio in the NiO x films, with the details given in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2a,b shows the Ni 2p spectra of the pristine NiO x and PSSNa-modified NiO x films. By fitting the XPS results, 16 it can be seen that Ni 2+ and Ni 3+ components exist in both films, and the signals at 853.9 eV are attributed to the NiO and the 855.6 and 857.5 eV signals correspond to the Ni 2p of Ni 2 O 3 and NiOOH, respectively. 32−34 It is found that the PSSNa modification increases the Ni 3+ /Ni 2+ ratio in the NiO x films, with the details given in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…For PeLEDs, the device performance is dependent on not only the perovskite-emitting layer but also the bottom hole transport materials (HTMs), which can affect both the hole injection efficiency and the perovskite film quality. , Poly­(3,4-ethyenedioxythiophene):poly­(styrene sulfonate) (PEDOT:PSS) is a widely used HTM in PeLEDs due to the advantages of easy processability and good carrier transport capability. , However, the inherent acidity and hygroscopicity of PEDOT:PSS would inevitably deteriorate the electrode and perovskite, leading to undesirable perovskite films and less-ideal LED device efficiency and stability. As an inorganic p-type semiconductor, NiO x is an alternative HTM for PeLEDs due to the attractive properties such as high optical transparency, good chemical and physical stability, and outstanding hole transporting ability as well as electron-blocking ability. Lee et al found that the use of the NiO x film, in comparison with PEDOT:PSS, enabled the growth of higher crystalline perovskite with reduced trap density of states, resulting in improved optical properties and stability of PeLEDs. Wang et al constructed green PeLEDs using NiO x HTM and achieved a threefold improvement in EQE and lifetime compared to the devices based on PEDOT:PSS.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, strategies have been explored to fabricate perovskite luminescent films and LEDs in ambient air. [16][17][18][19][20] For example, Liu et al report the fabrication of quasi-2D formamidinium lead bromide (FAPbBr 3 ) perovskite films, and realize efficient green LEDs. [16] However, the humidity and temperature of the environment have to be strictly controlled, which is unfavorable for low-cost industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…When processing in a high humidity air, the commonly used poly(3,4ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS) hole transport layer (HTL) can easily adsorb water and deteriorate the perovskite films. [18,19] To overcome this issue, in our recent work, we utilized more hydrophobic self-assembled monolayer (SAM) to replace the PEDOT:PSS, which enabled successful deposition of quasi-2D CsPbBr 3 perovskite films under ambient air with humidity up to 60%. [19] Nevertheless, the nonradiative losses at the interface and in the perovskite films are still prominent, leading to unsatisfactory performance of the air-processed LEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation